2016
DOI: 10.2147/tcrm.s112302
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction among type 2 diabetic female Egyptian subjects

Abstract: PurposeHigh prevalence of thyroid disorders is more common in type 1 diabetes compared to type 2 diabetes, due to associated autoimmunity. Hypothyroidism is the most common disorder. The objective was to assess the prevalence of thyroid dysfunction among type 2 diabetic Egyptian females and to find the correlation between metabolic syndrome components and autoimmune thyroid dysfunction.Materials and methodsThe study included 62 type 2 diabetic Egyptian females and 27 sex- and age-matched controls. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
4
11
0
2
Order By: Relevance
“…Previous studies have found that the prevalence of thyroid dysfunction is significantly higher in patients with T2DM than in the normal population. 18,25 In patients with T2DM, hypothyroidism is the most common type of thyroid dysfunction, with the incidence ranging from 18.3% to 45.2%. 18,25,26 The differences in the above results may be related to different detection methods, different races, and sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found that the prevalence of thyroid dysfunction is significantly higher in patients with T2DM than in the normal population. 18,25 In patients with T2DM, hypothyroidism is the most common type of thyroid dysfunction, with the incidence ranging from 18.3% to 45.2%. 18,25,26 The differences in the above results may be related to different detection methods, different races, and sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…18,25 In patients with T2DM, hypothyroidism is the most common type of thyroid dysfunction, with the incidence ranging from 18.3% to 45.2%. 18,25,26 The differences in the above results may be related to different detection methods, different races, and sample sizes. The present study showed that FT 4 level in T2DM combined with NAFLD was significantly lower than control group (median FT 4 0.89 vs 1.08, p < 0.001), while TSH level was significantly higher compared with the T2DM group, and the difference was significant (median TSH 2.85 vs 2.28, p < 0.05) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S druge strane, produžena upotreba lijekova iz grupe derivata sulfonilureje predisponira smanjenje funkcije štitne žlijezde i povećava rizik od karcioma štitnjače. Povećana koncentracija TSH (čak i unutar referentnih vrijednosti) povećava rizik od karcinoma štitnjače [14,15,16] 7,8]. Studija provedena u Istočnom Nepalu registrovala je prevalenciju hipotireoze od 10,7% (dvije trećina ima subkliničku hipotireozu).…”
Section: Introductionunclassified
“…Studija provedena u Istočnom Nepalu registrovala je prevalenciju hipotireoze od 10,7% (dvije trećina ima subkliničku hipotireozu). Do sličnih rezultata došla je i grupa autora iz Egipta ispitujući disfunkciju štitne žlijezde kod žena oboljelih od T2DM [7,8]. Prevalencija smanjenja tiroidne funkcije kod oboljelih od T2DM u Velikoj Britaniji iznosila je 13,4%, sa značajno većom učestalošću (37,4%) kod ženao boljelih od T2DM u odnosu na muškarce sa T2DM (6,9%).…”
Section: Introductionunclassified